Reocclusion of Recanalized Arteries during Intra-arterial Thrombolysis for Acute Ischemic Stroke - Qureshi, Adnan I.; Siddiqui, Amir M.; Kim, Stanley H.; Hanel, Ricardo A.; Xavier, Andrew R.; Kirmani, Jawad F.; Suri, M. Fareed K.; Boulos, Alan S.; Hopkins, L. Nelson (American Journal of Neuroradiology, 2004)
BACKGROUND AND PURPOSE: Early reocclusion of recanalized arteries has been observed after thrombolysis for acute coronary occlusion and has been attributed to platelet activation after exposure to thrombolytic agents. We conducted a retrospective study to determine the rate of reocclusion during intra-arterial thrombolysis for acute ischemic stroke and the effect of reocclusion on functional outcome.METHODS: Patients treated for acute ischemic stroke at our center between September 2000 and May 2002 received a maximum total dose of 4 U of reteplase intra-arterially in 1-U increments via superselective catheterization. Pharmacologic thrombolysis was supplemented by mechanical thrombolysis with balloon angioplasty or snare manipulation at the occlusion site. Angiography was performed after each unit of reteplase or mechanical maneuver, and the images were interpreted by a blinded reviewer. Reocclusion was defined as partial or complete initial recanalization with occlusion recurring at the same site as documented by angiography during the endovascular treatment. Reocclusions were treated by further pharmacologic and/or mechanical thrombolysis according to the discretion of the treating physician. Clinical evaluations were performed before and 24 hr, 7 to 10 days, and 1 to 3 months after treatment.RESULTS: Forty-six consecutive patients underwent intra-arterial thrombolysis. Reocclusion was observed in eight (17%). Among these patients, initial sites of occlusion were in the following arteries: intracranial internal carotid artery (n = 2), M1 segment of the middle cerebral artery (n = 3), M1 and M2 segments of the middle cerebral artery (n = 2), and basilar artery (n = 1). The mean initial National Institutes of Health Scale score for these eight patients was 23.3 ± 6.2; mean time from symptom onset to treatment was 4.4 ± 1.2 hr. The reocclusions were treated by using additional doses of reteplase alone (n = 1), reteplase with snare maneuver and/or angioplasty (n = 5), reteplase with angioplasty or snare and then stent placement (n = 1), and angioplasty with stent placement (n = 1). The reocclusions resolved in six of eight patients after further treatment. Six patients died and two survived but were severely disabled at 1 month (modified Rankin Scale scores of 4 and 5, respectively). Independent functional outcome scores (modified Rankin Scale scores of 0–2) were significantly lower among patients with angiographically shown reocclusion than in those without (0 of 8 versus 17 of 38, P = .02).CONCLUSION: Reocclusion occurs relatively frequently during intra-arterial thrombolysis for ischemic stroke and seems to be associated with poor clinical outcomes.